2012
DOI: 10.1111/boc.201100061
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical assessment of aquaporin‐9 as principal facilitative pathway in mouse liver import of glucogenetic glycerol

Abstract: Overall, these results experimentally prove major functional significance for AQP9 in maximising liver glycerol import during states requiring increased glucose production. If any, alternative facilitated pathways would be of minor importance in transporting glucogenetic glycerol into hepatocytes during starvation. Refining the understanding of liver AQP9 in metabolic and energy homeostasis may reveal helpful for therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 32 publications
(57 reference statements)
7
97
1
2
Order By: Relevance
“…In contrary, there was no NMD in our study, and reviewed the other split-site mutations previously reported, no NMD was found too [4,5]. Fourth, some studies demonstrated that glycerolutilization by the cells (especially, hepatocytes) is rate-limited by the membrane permeation step, rather than the GK step [13][14][15]. AQP9, an aquaglyceroporin, has been reported to be of great significance in glycerol membrane permeation step [13][14][15].…”
Section: Citation: Zeng L Mei L Tan H Li H Lv W Et Al (2017) a contrasting
confidence: 64%
See 1 more Smart Citation
“…In contrary, there was no NMD in our study, and reviewed the other split-site mutations previously reported, no NMD was found too [4,5]. Fourth, some studies demonstrated that glycerolutilization by the cells (especially, hepatocytes) is rate-limited by the membrane permeation step, rather than the GK step [13][14][15]. AQP9, an aquaglyceroporin, has been reported to be of great significance in glycerol membrane permeation step [13][14][15].…”
Section: Citation: Zeng L Mei L Tan H Li H Lv W Et Al (2017) a contrasting
confidence: 64%
“…Fourth, some studies demonstrated that glycerolutilization by the cells (especially, hepatocytes) is rate-limited by the membrane permeation step, rather than the GK step [13][14][15]. AQP9, an aquaglyceroporin, has been reported to be of great significance in glycerol membrane permeation step [13][14][15]. Expression of AQP9 is influenced by gender and disease state.…”
Section: Analysis Of Gk Expression By Real-time Quantitative Pcrmentioning
confidence: 99%
“…This 10-fold increase was accompanied by a two-fold increase in hepatocyte plasma membrane glycerol permeability, which was reversed by addition of phloretin (an apple polyphenol that inhibits AQP9, AQP3 and several non-AQP membrane channel proteins including the SGLT1&2 glucose transporters and UT-A urea channels [74]). The increase was abolished in AQP9 -/-mice [75]. Fasted AQP9 -/-mice have elevated plasma glycerol compared to wild-type [75,76].…”
Section: Aqp9mentioning
confidence: 82%
“…The increase was abolished in AQP9 -/-mice [75]. Fasted AQP9 -/-mice have elevated plasma glycerol compared to wild-type [75,76]. In addition, plasma glucose concentration was decreased [76], indicating a gluconeogenetic deficiency.…”
Section: Aqp9mentioning
confidence: 87%
“…Aquaporin 9 (AQP9) is a broad-selectivity neutral solute channel that facilitates the hepatic uptake of glycerol (3,29,32,33). The importance of AQP9 as a facilitator of hepatic glycerol uptake is illustrated by the increased plasma glycerol levels found in AQP9 KO mice (29).…”
mentioning
confidence: 99%